Petri net-based Model for Packet Flows - Plėštys, R.; Lagzdinytė, I. (Elektronika ir Elektrotechnika, 2003)
Formal description method based on Petri net model is proposed. Model takes into account the real packet traffic parameters. Given analytical expressions describe the relations between the Petri net characteristics and traffic source parameters. Consistent patterns of Petri net parameters variations due to packet flow parameters are listed. It is shown that in case when average packet rate and packet rate at the current moment have common divisor, Petri net characteristics are defined with local minimum: if ratio of average packet rate and packet rate at the current moment is an integer number, packet flow becomes periodical and Petri net parameters gets minimal values. Packet flow and Petri net characteristics time diagrams for different service category packet flows are given as well. Ill.7, bibl.4 (in Lithuanian; summaries in Lithuanian, English, Russian).